The Lesbianism of Celie in the Novel “The Color Purple” by Alice Walker (Psychological Approach) - Ramli Ramli; Muhammad Hairul Rizal (English Department FBS UNP, 2021)
The aims of the research are to analyse the aspects dan the factors that influence Celie, the main character being a lesbian in the novel “The Colour Purple” by Alice Walker. The research applied descriptive method by using psychological approach through the principle of Adler’s personality theory. The data source was taken from all the words, dialogues, phrases, and, sentences in Alice Walker's novel